Organizational Performance: A Survey on the Culinary Sector Business During the Economic Recovery Period - Irwan Yantu (Jambura Science of Management, 2022)
This study aims to measure the extent to which the company's performance during the post-covid recovery period. This study involved business owners in the food and beverage sector in Gorontalo as respondents, because this sector was quite affected by the social restriction policy in order to break the chain of virus spread. The research method used is a quantitative method. The research data was collected using a questionnaire containing 30 questions about the condition of the company when the restriction policy was implemented and about the condition of the company after the recovery. The results showed that as long as the restrictions were applied, the company had difficulty serving customers. Due to limited operational time and decreased number of visits. Respondents admitted that at the beginning of the implementation of the restrictions, the company's revenue had experienced a contraction. However, entering the recovery period, the company's condition began to improve. Statistical analysis also proves that the company's performance is influenced by the implementation of social restriction policies. The results of the study concluded that the implementation of the PSBB policy had a significant effect on business performance in the food and beverage sector in Gorontalo. The effect given by the implementation of PSBB on company performance is 39.1%.